2008
DOI: 10.1088/0268-1242/23/8/085026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dot size distribution and interlayer thickness on the optical property of closely stacked InAs/GaAs quantum dots with growth interruption

Abstract: We investigated the effect of dot size distribution and interlayer thickness on the optical property of closely stacked self-assembled InAs/GaAs quantum dot (QD) structures with growth interruption for 30 s using an As 2 source. The structural property was optimized by changing the growth parameters, such as growth temperature, growth time and group III/V ratio. As the stacking number was increased, the size of truncated pyramid-shaped QDs became larger in both height and width, maintaining an on-top vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…During the deposition of the InAs layer to form InAs QDs in the temperature range 480-540 °C for 32 s, the reflection high energy electron diffraction pattern changed from streaky to spotty while revealing Chevron's angle at 28 s after the InAs deposition, indicating InAs QD formation [27]. This also provides evidence that a growth duration of 20 s is too short to form InAs QD.…”
Section: Effect Of Growth Parameter Variation On Inas Qd Formationmentioning
confidence: 77%
“…During the deposition of the InAs layer to form InAs QDs in the temperature range 480-540 °C for 32 s, the reflection high energy electron diffraction pattern changed from streaky to spotty while revealing Chevron's angle at 28 s after the InAs deposition, indicating InAs QD formation [27]. This also provides evidence that a growth duration of 20 s is too short to form InAs QD.…”
Section: Effect Of Growth Parameter Variation On Inas Qd Formationmentioning
confidence: 77%
“…the molecular beam epitaxy (MBE) method [7,8]. A uniform size and spacing between III-V QDs and a high in-plane density of a 2D array of III-V QDs are at present difficult to achieve with self-organized bottom-up processes [9,10]. Considering the design of a III-V QD IBSC [3,11], it is very important to uniformly control the diameter and height of III-V QDs to create a uniform intermediate band for the application in thirdgeneration solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we perform a systematic investigation on the growth parameters of InAs/GaAs closely stacked QDs in order to control their polarization behavior, namely the surface reconstruction time of GaAs spacer, the spacer thickness and the number of QD layers [13]. In particular, we found that in order to enhance the TM/TE intensity ratio, the most effective parameter is the reconstruction time of the GaAs spacer before the subsequent QD deposition.…”
Section: Introductionmentioning
confidence: 99%